A gut-restricted glutamate carboxypeptidase II inhibitor reduces monocytic inflammation and improves preclinical colitis - Peters, Diane E; Norris, Lauren D; Tenora, Lukáš; Šnajdr, Ivan; Ponti, András K; Zhu, Xiaolei; Sakamoto, Shinji; Veeravalli, Vijayabhaskar; Pradhan, Manisha; Alt, Jesse; Thomas, Ajit G; Majer, Pavel; et al. (Science translational medicine, 2023)
There is an urgent need to develop therapeutics for inflammatory bowel disease (IBD) because up to 40% of patients with moderate-to-severe IBD are not adequately controlled with existing drugs. Glutamate carboxypeptidase II (GCPII) has emerged as a promising therapeutic target. This enzyme is minimally expressed in normal ileum and colon, but it is markedly up-regulated in biopsies from patients with IBD and preclinical colitis models. Here, we generated a class of GCPII inhibitors designed to be gut-restricted for oral administration, and we interrogated efficacy and mechanism using in vitro and in vivo models. The lead inhibitor, (S)-IBD3540, was potent (half maximal inhibitory concentration = 4 nanomolar), selective, gut-restricted (AUCcolon/plasma > 50 in mice with colitis), and efficacious in acute and chronic rodent colitis models. In dextran sulfate sodium-induced colitis, oral (S)-IBD3540 inhibited >75% of colon GCPII activity, dose-dependently improved gross and histologic disease, and markedly attenuated monocytic inflammation. In spontaneous colitis in interleukin-10 (IL-10) knockout mice, once-daily oral (S)-IBD3540 initiated after disease onset improved disease, normalized colon histology, and attenuated inflammation as evidenced by reduced fecal lipocalin 2 and colon pro-inflammatory cytokines/chemokines, including tumor necrosis factor-α and IL-17. Using primary human colon epithelial air-liquid interface monolayers to interrogate the mechanism, we further found that (S)-IBD3540 protected against submersion-induced oxidative stress injury by decreasing barrier permeability, normalizing tight junction protein expression, and reducing procaspase-3 activation. Together, this work demonstrated that local inhibition of dysregulated gastrointestinal GCPII using the gut-restricted, orally active, small-molecule (S)-IBD3540 is a promising approach for IBD treatment.
Keywords: Colon; Disease Models, Animal; modely nemocí na zvířatech; myši; kolon; kolitida; lidé; Humans; glutamátkarboxypeptidasa II; Mice; Animals; zánět; myši inbrední C57BL; cytokiny; idiopatické střevní záněty; Glutamate Carboxypeptidase II; Cytokines; zvířata; Inflammatory Bowel Diseases; Mice, Inbred C57BL; Colitis; Inflammation